Heavy metal content in selected flavouring plants and in ultra-basic soil of Felda Rokan Barat,Negeri Sembilan, Malaysia - Sahibin Abd. Rahim,; Wan Mohd. Razi Idris,; Zulfahmi Ali Rahman,; Tukimat Lihan,; Ramlan Omar,; Liew, Kah Yan (Universiti Kebangsaan Malaysia, 2012)
A study was carried out at an ultrabasic soil area in Felda Rokan Barat (FRB), Negeri Sembilan. Twenty plants of samples namely chili, turmeric, pandan and lemon grass were collected randomly for the determination of heavy metal contents such as Fe, Cd, Co, Cu, Mn, Ni, Pb, Cr and Zn. Heavy metals in plants were extracted by wet digestion method, whereas available and resistant heavy metals in soil were extracted by sequential extraction. Total heavy metals content in the soil were obtained by summation of resistant and available heavy metals. Heavy metals content in soil and plant extract were determined by using the Flame Atomic Absorption Spectrophotometer (FAAS). Results showed that Fe was the dominant composition in soil in the study area while Cd concentration was very low with values of < 10 mg/kg. The range of heavy metals concentration in soils were Fe (2618.4 to 4248 mg/kg), Mn (240.9 to 741.9 mg/kg), Zn (81.9 to 324.8 mg/kg), Cr (46.8 to 438.7 mg/kg), Cu (15.7 to 81.7 mg/kg), Pb (14.9 to 116.8 mg/kg), Ni (10.1 to 545.6 mg/kg), Cd (5.6 to 10.6 mg/kg) dan Co (0.8 to 126.1 mg/kg). Available Fe recorded the highest value in all of the plant substrates followed by Mn, Zn, Pb, Ni, Cr, Cu, Co and Cd. Based on percentage of availability Mn, Pb and Zn are considered most available by plant with availability percentage of 8 to 10%. Concentration of Fe, Mn, Ni and Zn were high in all parts of plants compared to the other metals. The value of biological absorption coefficient (BAC) in chili, turmeric, pandan and lemon grass were in the range of 0.02-0.36, 0.03-0.41, 0.03-0.63 and 0.03-1.15, respectively. It can be concluded that the uptake of heavy metals by plants were normal even though the heavy metals concentration in the ultrabasic soil was high.